Effect of in situ annealing on the structural and electrical properties and infrared photodetection of III-Sb on GaAs using interfacial misfit array - Jia, Bo Wen (2019)
This work presents the effects of in situ thermal annealing under antimony overpressure on the structural, electrical, and optical properties of III-Sb (GaSb and InSb) grown on (100) GaAs using an interfacial misfit array to accommodate the lattice mismatch. Both the sample growth and the in situ thermal annealing were carried out in the in the molecular beam epitaxy system, and the temperature of the as-grown sample was increased to exceed its growth temperature during the annealing. X-ray diffraction demonstrates nearly fully relaxed as-grown and annealed III-Sb layers. The optimal annealing temperatures and durations are for 590 °C, 5 min for GaSb and 420 °C, 15 min for InSb, respectively. In situ annealing decreased the surface roughness of the III-Sb layers. X-ray reciprocal space mapping and transmission electron microscopy observation showed stable interfacial misfit arrays, and no interfacial diffusion occurred in the annealed III-Sb layers. A Hall measurement of unintentionally doped III-Sb layers showed greater carrier mobility and a lower carrier concentration in the annealed samples at both 77 and 300 K. In situ annealing improved the photoresponsivity of GaSb and InSb photoconductors grown on GaAs in the near- and mid-infrared ranges, respectively.